2016
DOI: 10.1039/c5ra22749f
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional application of sodium cobaltate as a catalyst and captor through CO oxidation and subsequent CO2 chemisorption processes

Abstract: Sodium cobaltate works as a bifunctional material, in the catalysis of CO oxidation and subsequent CO2 chemisorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…Previous works have shown that sodium cobaltate has different physicochemical CO 2 capture properties and other catalytic processes involving carbon oxides, such as carbon monoxide oxidation, water gas shift, and reforming reactions, although this ceramic does not have a Na/Co molar ratio as high as other alkaline ceramics . Therefore, it is important to understand the CO 2 capture properties of this ceramic at low temperatures, induced by the presence of water vapor, as under dry conditions NaCoO 2 is not able to trap CO 2 chemically at temperatures lower than 200 °C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous works have shown that sodium cobaltate has different physicochemical CO 2 capture properties and other catalytic processes involving carbon oxides, such as carbon monoxide oxidation, water gas shift, and reforming reactions, although this ceramic does not have a Na/Co molar ratio as high as other alkaline ceramics . Therefore, it is important to understand the CO 2 capture properties of this ceramic at low temperatures, induced by the presence of water vapor, as under dry conditions NaCoO 2 is not able to trap CO 2 chemically at temperatures lower than 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in reactions (3) and (4), the formation of a cobalt oxide is proposed, as for this type of alkaline ceramics, CO 2 capture always leads to the formation of carbonates and the corresponding metal oxide. [3,[54][55][56] As stated in the literature, [64,65] NaCoO 2 does not chemisorb CO 2 at temperatures lower than 200 C, on dry conditions. Thus, water vapor highly activates CO 2 chemisorption at lower temperatures, forming two different carbonate phases, Na 2 CO 3 (as in dry conditions) and NaHCO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations